Barriers to technological and non-technological innovation - Musibau, Ajagbe Akintunde (iiste, 2015)
The complication of innovation activities has resulted to a massive increase in the adoption of external networks by Small, Medium to Large (SML) firms. The main objective of this study is to investigate the barriers to technological and non-technological innovation activities in SML firms both in the service and manufacturing sectors in Malaysia. It was reported that the gathering and distribution of data on innovation activities of a nation is unquantifiable to the prosperity and development of that nation. However, National Innovation Survey (NIS) in Malaysia dates back to the initial survey carried out in 1994 to gather data on innovation activities among SML firms in areas such as inventions, product developments, process creation, development and organizational change. The research philosophy adopted was multiple regression analysis executed on the collected interview data. Aside that, T-tests was also used to compare the means of variables between the randomly chosen domestic and foreign companies. In this research, the data was analyzed using Statistical Product and Service Solution (SPSS) version 18. Descriptive data analysis were used to explain the findings and were presented in the forms of tables and figures to describe the amount of innovation activities and the barriers to innovation activities in both the manufacturing and services sectors.